Blood parameters and pathological lesions in pigs experimentally infected with Vietnam's first isolated African swine fever virus - Oh, Sang-Ik; Nguyen, Thi Thu Huyen; Yang, Myeon-Sik; Nga, Bui Thi To; Bui, Vuong Nghia; Le, Van Phan; Yi, Seung-Won; Kim, Eunju; Hur, Tai-Young; Lee, Hu Suk; Kim, Bumseok (Frontiers in Veterinary Science, 2022)
African swine fever virus (ASFV) is a notable virus and one of the most serious global threats to the pig industry. Improving awareness about host–virus interactions could facilitate the understanding of the disease pathogenesis. Therefore, we investigated changes in blood parameters, viral loads, and pathological changes in ASFV-inoculated pigs according to the time of death after the onset of viremia. For the analyses, the ASFV-infected pigs (n = 10) were divided into two groups (five pigs/group) according to their time of death after the onset of viremia. The blood cell count dynamics and serum biochemistry profiles were similar between the groups; however, viral load distribution was different. A comparison of the histopathological changes and immunohistochemistry results between the two groups indicated that the lymphoid system, particularly the spleen, was more damaged in the early stage of the disease than in the last stage. Additionally, the virus-induced lesions in other organs (liver and kidney) were more severe in the late stage than in the early stage. Our findings provide invaluable information on the characteristics of blood parameters and pathological lesions in pigs infected with the Asia-epidemic ASFV strain and the course of ASF, targeting internal organs in pigs. Overall, this study characterizes the host-pathogen interaction in ASFV infection, offering insight for the establishment of ASF control strategies.